The differences in the concept of self among the superior and non-outstanding students among the high school students in Abha - Alfageih, Hussain Balghasem (Journal of Educational and Psychological Sciences, 2020)
The objectives of the study: Identify the differences in the concept of the self between students and non-students in secondary school. Identify the differences between the six dimensions of self concept of students and non-students in secondary school.Study: researchers have used the descriptive relational.Sample: the sample consisted of 115 students of grade I، II and III of secondary gifted and non-gifted to the city of Abha.Study tools: we used the following tool: Self concept scale for adolescents، Mary (2009) Statistical methods: the researcher used statistical methods: The percentages and duplicates. Test.The results of the study: researchers the following results: There are significant differences in self-concept between gifted and non-gifted high school students in the city of Abha. There are significant differences in the concept of self ethical and moral self-concept between gifted and non-gifted high school students in the city of Abha. There are no statistically significant differences in the concept of the physical self, the concept of the mental self, the concept of the emotional self, and the concept of the social self between the excelling and the non-excelling among high school students in Abha.
Keywords: differences; self concept; superior students; high school